Why the new coronavirus is an asset for terrorists (republicação) - Lopes, J. (Blog Changing World (Cei-Iscte), 2020)
This piece argues that terrorist activity is likely not to decrease because the coronavirus crisis is a potential asset for terrorists. I discuss seven reasons why is it an asset. (This article was also published in the Blog Apostrophe Project).